2017
DOI: 10.1177/2045125317741449
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine discontinuation in early schizophrenia: a retrospective case note review of patients under an early intervention service

Abstract: Aim:Research in patients with treatment-resistant schizophrenia has demonstrated that clozapine discontinuation is associated with poor outcomes. There is, however, a paucity of research investigating the impact of clozapine discontinuation specifically in younger patients with more recent onset schizophrenia. A case note review was therefore conducted to ascertain medium-term prognoses in patients with treatment-resistant schizophrenia under an early intervention service (EIS) following clozapine discontinuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The number of patients in each study was 106 in one RCT 13 ; 190 in one retrospective study 12 ; 1,008 in one mirror-image study 26 ; 2,250 in one retrospective cohort study 17 ; and small sample sizes (n<100) for the remaining studies. All studies included patients with schizophrenia spectrum disorders, 12 14 16 18 19 23 23 25 27 32 32 34 37 exclusively included patients with TRS, two 11 35 included both patients with TRS and non-TRS, and 14 12 13 15 17 20 20 22 26 28 28 29 31 36 37 did not clearly state whether patients had TRS or non-TRS ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients in each study was 106 in one RCT 13 ; 190 in one retrospective study 12 ; 1,008 in one mirror-image study 26 ; 2,250 in one retrospective cohort study 17 ; and small sample sizes (n<100) for the remaining studies. All studies included patients with schizophrenia spectrum disorders, 12 14 16 18 19 23 23 25 27 32 32 34 37 exclusively included patients with TRS, two 11 35 included both patients with TRS and non-TRS, and 14 12 13 15 17 20 20 22 26 28 28 29 31 36 37 did not clearly state whether patients had TRS or non-TRS ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of clozapine treatment varied considerably from weeks to years. Among the 18 studies 11 11 11 12 14 16 19 21 22 24 25 27 28 30 32 32 33 34 36 that stated reasons for clozapine discontinuation, we classified the reasons into the following six categories: inefficacy, intolerance, nonadherence, patient or clinician decision, study design, and other. Among the 15 studies 11 13 15 18 20 23 28 28 30 32 33 35 35 37 that described a clozapine discontinuation strategy, six studies 18 29 30 32 37 reported abrupt discontinuation and nine studies 11 13 15 20 23 28 33 35 36 reported gradual discontinuation ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is the only effective drug for refractory schizophrenia. However, although CLZ is effective in treating psychosis, it may need to be discontinued in several cases such as pericarditis ( 11 ), agranulocytosis, and antipsychotic malignant syndrome ( 12 ). In addition, there may be a variety of withdrawal reactions such as autonomic nervous system symptoms, psychosis, gastrointestinal tract and serotonin discontinuation symptoms during drug withdrawal ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 In some circumstances, clozapine has been discontinued successfully after symptom remission. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…8 In some circumstances, clozapine has been discontinued successfully after symptom remission. 9,10 Since the widespread use of clozapine, it has been recognised that stopping clozapine can lead to marked deterioration in clinical status in patients. Whilst this has been attributed largely to a relapse of the underlying mental disorder, it has become increasingly recognised that this may also be attributable to clozapine withdrawal symptoms.…”
Section: Introductionmentioning
confidence: 99%